ANALISIS YURIDIS PERBANDINGAN PUTUSAN PENGADILAN TERHADAP APARATUR SIPIL NEGARA DAN MASYARAKAT YANG MELAKUKAN TINDAK PIDANA DI INDONESIA - Janri Aldo S; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Torture is defined as an act that is done deliberately to cause pain (pijn) for wounds (letsel) on another person's body. Others understand that persecution is "intentionally causing pain or injury, that intention must be included in the accusation letter". Persecution as a form of crime is a social problem that is difficult to eliminate in society. Persecution can occur anywhere and anytime and anyone can commit these crimes. One of them was an incident in the Meranti Islands Regency, which was carried out openly and jointly in public and resulted in the death of unscrupulous members of the Meranti Islands resort police, and clearly violated the rules of the police law. In this problem there are two main problems, namely , What is the basis for the judge's consideration in making the decision and how ideal is the criminal law against members of the Police who have committed serious acts of torture resulting in death. Based on the results of research and discussion, the authors can draw the conclusion that the factors causing the crime of persecution committed by the State Civil Apparatus in the Meranti Islands Regency are internal factors and external factors. Internal factors are factors that come from within the perpetrator, the perpetrator feels upset and emotional at the time of the incident so that the lack of self-control by the State Civil Apparatus, these emotional factors have an impact on the perpetrator to commit a crime so that there is persecution by the perpetrator against the victim. As well as the factor of lack of awareness of the existence of a code of ethics that applies as the perpetrator is a State Civil Apparatus who carries out state duties as a good example for society. External factors are factors from outside the perpetrator where economic factors, weather factors, and circumstances can also greatly influence the occurrence of crime. Keywords: Persecution, Civil Servants.